2019
DOI: 10.1007/s10482-019-01269-5
|View full text |Cite
|
Sign up to set email alerts
|

Paraburkholderia strydomiana sp. nov. and Paraburkholderia steynii sp. nov.: rhizobial symbionts of the fynbos legume Hypocalyptus sophoroides

Abstract: Twelve nodulating Paraburkholderia strains isolated from indigenous South African fynbos legume Hypocalyptus sophoroides were investigated to determine their taxonomic status.Genealogical concordance analysis, based on six loci (16S rRNA, atpD, recA, rpoB, lepA and gltB), revealed that they separate into two consistent and exclusive groups. Average nucleotide identity and DNA-DNA hybridisation comparisons indicated that they were sufficiently divergent from their closest known phylogenetic relatives (Parabur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…Most of the rhizobial species occurring in the CCR can establish nitrogen‐fixing symbioses with multiple papilionoid species (Table 2). Future exploration of the legume–rhizobium symbiosis in the region will likely show that this is also true for bacteria that have been reported from single host species (e.g., P. steynii and P. strydomiana that nodulate Hypocalyptus sophoroides and P. rhynchosiae that nodulates Rhynchosia ferulifolia ) (Beukes, Steenkamp, et al., 2019; De Meyer, Cnockaert, Ardley, Trengove, et al., 2013; Table 2). Likewise, many CCR papilionoids are promiscuous in terms of nodulating partner as several species are capable of nodulating with multiple Paraburkholderia species.…”
Section: Paraburkholderia and Papilionoid Legumesmentioning
confidence: 91%
See 2 more Smart Citations
“…Most of the rhizobial species occurring in the CCR can establish nitrogen‐fixing symbioses with multiple papilionoid species (Table 2). Future exploration of the legume–rhizobium symbiosis in the region will likely show that this is also true for bacteria that have been reported from single host species (e.g., P. steynii and P. strydomiana that nodulate Hypocalyptus sophoroides and P. rhynchosiae that nodulates Rhynchosia ferulifolia ) (Beukes, Steenkamp, et al., 2019; De Meyer, Cnockaert, Ardley, Trengove, et al., 2013; Table 2). Likewise, many CCR papilionoids are promiscuous in terms of nodulating partner as several species are capable of nodulating with multiple Paraburkholderia species.…”
Section: Paraburkholderia and Papilionoid Legumesmentioning
confidence: 91%
“…Of the 20 known rhizobial Paraburkholderia species, eight were found in the CCR. These include the first beta‐rhizobial species to be recognized, P. tuberum (Moulin et al., 2001; Vandamme et al., 2002) as well as P. kirstenboschensis , P. strydomiana , P. steynii , P. dilworthii , P. sprentiae , P. dipogonis and P. rhynchosiae (Beukes, Steenkamp, et al., 2019; De Meyer, Cnockaert, Ardley, Maker, et al., 2013; De Meyer, Cnockaert, Ardley, Trengove, et al., 2013; De Meyer et al., 2014; Sheu et al., 2015; Steenkamp et al., 2015).…”
Section: Paraburkholderia and Papilionoid Legumesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that bacterial groups evolved in this biome to be hyper-diverse and in many cases some species are only found in this part of the world as was the case with Burkholderia [91,92] and Paraburkholderia [93]. This group of bacteria functions as symbionts of plants to acquire nitrogen through fixation [94].…”
Section: Bacteriamentioning
confidence: 99%
“…appears to have nodulation genes that are closely related and only form nodules in the presences of fynbos papilionoid legumes [95]. Numerous studies isolated and characterised species from this bacterial group, including some novel strains [91,93,96]. Most of the strains isolated from fynbos plants are shown to be highly adapted to low pH environments, consistent with the fynbos soils [97].…”
Section: Bacteriamentioning
confidence: 99%